E-Learning of Information Technology for Desa Pagar Pinang - Sirait, Debora (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The importance of information technology and technology is felt to be important to empower villages. So that it is expected to be able to maximize the use of cross-sectoral development ranging from the economy, health, education, to local government management. Information Technology has been widely used to support business processes that occur in companies, both in the economic and banking fields. With the presence of applications and services for e-business, e-commerce, e-banking and others. The need for time and cost efficiency causes every business person to feel the need to apply information technology in the work environment. In agricultural economics, farm yields, crop yields, or very often abbreviated as yields, are quantities that describe the amount of agricultural harvested products obtained in one area of ​​land in one production cycle.